Mechanical and dielectric properties of graphene incorporated polypropylene nanocomposites using polypropylene-graft-maleic anhydride as a compatibilizer. (1st December 2017) - Li, Chao-Qun; Zha, Jun-Wei; Long, Hua-Qian; Wang, Si-Jiao; Zhang, Dong-Li; Dang, Zhi-Min
Abstract: To achieve uniform dispersion of graphene in polypropylene, polypropylene- graft -maleic anhydride (PP- g -MA) as compatibilizer was compounded with graphene to obtain masterbatch, and then melt blended with polypropylene using a micro-compounder. Raman study showed the strong interfacial interaction between the surface of functionalized graphene sheets (FGS) and the compatibilizer, while morphologic study indicated the homogeneous dispersion of graphene in polypropylene. Remarkable enhancements in mechanical, thermal and dielectric properties were obtained at low graphene loading. At an effective graphene content of 1.5 wt%, the tensile strength and storage modulus of polypropylene increased by 18% and 33%, respectively. The electrical percolation threshold of the nanocomposites is about 0.55 vol%, which is lower than most of previously reported polypropylene composites prepared by similar melt processing. Near the percolation threshold (0.535 vol% graphene), the dielectric permittivity increased to 15.2 and the loss tangent was kept as low as 0.20 at 10 3 Hz.